Memory modification and authenticity: a narrative approach - Leuenberger, M (Springer, 2022)
The potential of memory modification techniques (MMTs) has raised concerns and sparked a debate in neuroethics, particularly in the context of identity and authenticity. This paper addresses the question whether and how MMTs influence authenticity. I proceed by drawing two distinctions within the received views on authenticity. From this, I conclude that an analysis of MMTs based on a dual-basis, process view of authenticity is warranted, which implies that the influence of MMTs on authenticity crucially depends on the specifics of how memory modification would eventually work. Therefore, I continue with a systematic analysis of possible properties of MMTs in which I distinguish between the dimensions of memories and the kinds of experiences that can be modified as well as the properties of the process of memory modification. The impact of MMTs on authenticity is analyzed regarding the possible properties of MMTs and based on a narrative approach to authenticity which fulfills the requirements of a dual-basis, process view of authenticity. Lastly, I explore the potential of MMTs to shift the balance between self-discovery and self-creation within authenticity and thereby alter the concept itself as well as the value of authenticity.